Mapping and Current Trends in Sustainable Communication: A Bibliometric View - Aslan, Ayşe; Öztürk, Mehtap; Eryeşil, Kemalettin (My University, 2024)
The aim of this study is to examine the development of the concept of sustainable communication in the business, management and communication literature through bibliometric analysis. Sustainable communication involves strategic, transparent dissemination of information integrating environmental, social, and economic factors, engaging stakeholders, promoting awareness, and emphasizing the interconnectedness of sustainability dimensions. The research problem lies in the absence of a comprehensive bibliometric study on sustainable communication, despite the abundance of studies in field of sustainability and communication. This study will fill this gap in the literature by utilizing the bibliometric analysis method and contributing to the existing literature. The situation underscores the significance of research. In line with this purposes, this study examines 2724 articles on sustainable communication, focusing on applied studies and focusing on the distribution of these articles, co-authorship, co-citation, and co-occurence of the authors who published them. As a result of the bibliometric analysis, it has been determined that the field of sustainable communication has continued to develop over the years and that the concepts of big data within the scope of Industry 4.0, green business, sustainable business, sustainable supply chain management, environmental performance, greenwashing, and the circular economy have come to the fore in recent years. The study’s findings can be beneficial to scholars as they reveal the current performance of authors, documents, as well as the progression of themes.
Keywords: Sustainability; Bibliometric Analysis; Communication; Web of Science.; Sustainable Communication